2016
DOI: 10.3389/fpsyg.2016.01329
|View full text |Cite
|
Sign up to set email alerts
|

Complexity As Key to Designing Cognitive-Friendly Environments for Older People

Abstract: The lived environment is the arena where our cognitive skills, preferences, and attitudes come together to determine our ability to interact with the world. The mechanisms through which lived environments can benefit cognitive health in older age are yet to be fully understood. The existing literature suggests that environments which are perceived as stimulating, usable and aesthetically appealing can improve or facilitate cognitive performance both in young and older age. Importantly, optimal stimulation for … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

3
34
0
1

Year Published

2018
2018
2023
2023

Publication Types

Select...
6
3

Relationship

1
8

Authors

Journals

citations
Cited by 75 publications
(38 citation statements)
references
References 162 publications
3
34
0
1
Order By: Relevance
“…The age of the cohort may also have contributed to the lack of response in high beta activity; it has been suggested that beta activity may be susceptible to change in older age (Gola et al 2012), in particular at higher frequencies (Christov and Dushanova 2016). The notion of varying complexity in order to achieve cognitive-friendly environments (Cassarino and Setti 2016) that help people navigate in older age, despite some level of cognitive decline, suggests that a lack of environmental complexity may result in sub-optimal cognitive stimulation; this may explain the absence of high beta activity in any of the walking routes presented in the data here.…”
Section: Discussionmentioning
confidence: 99%
“…The age of the cohort may also have contributed to the lack of response in high beta activity; it has been suggested that beta activity may be susceptible to change in older age (Gola et al 2012), in particular at higher frequencies (Christov and Dushanova 2016). The notion of varying complexity in order to achieve cognitive-friendly environments (Cassarino and Setti 2016) that help people navigate in older age, despite some level of cognitive decline, suggests that a lack of environmental complexity may result in sub-optimal cognitive stimulation; this may explain the absence of high beta activity in any of the walking routes presented in the data here.…”
Section: Discussionmentioning
confidence: 99%
“…Finally, it is important to consider the positive utility or intrinsic value of transport use for cognitive function (30). The bus ride itself may serve as a cognitively-stimulating environment or activity that directly benefits cognitive health (31).…”
Section: Discussionmentioning
confidence: 99%
“…These findings support ecological models of ageing (9) and theories of environmental design (25) which suggest that the level of stimulation coming from the surrounding environment has to be within a certain "optimal" range in order to promote adaptive cognitive responses, especially if functional limitations make us more susceptible to environmental demands. From a cognitive, information-processing viewpoint, an older person living in a more urbanised area is exposed to a more dynamically complex environment which stimulate cognitive skills that deal with novelty (7), multi-tasking, and making sense of complex perceptual information (5,22,26). On the other hand, animal and human studies suggest that overpopulation and crowding are associated with reduced cognitive control and impaired spatial memory because increasing distractibility and mental fatigue (27)(28)(29).…”
Section: Introductionmentioning
confidence: 99%
“…On the other hand, animal and human studies suggest that overpopulation and crowding are associated with reduced cognitive control and impaired spatial memory because increasing distractibility and mental fatigue (27)(28)(29). Within this perspective, low levels and, on the opposite, very high levels of urbanisation, should be the least supportive of cognitive functioning, the former being not stimulating enough, whereas the latter potentially overloading and cognitively detrimental (25,26), especially for an individual with limited functionality.…”
Section: Introductionmentioning
confidence: 99%